Pathological response and safety of albumin-bound paclitaxel as a neoadjuvant treatment for HER2-positive breast cancer compared to docetaxel combined with anti-HER2 therapy: a real-world study - Lyu, Zhidong; Gao, Linlin (Frontiers in Oncology, 2024)
This study aimed to retrospectively analyse the pathological response and safety of combining albumin-bound paclitaxel (nab-paclitaxel) or docetaxel with anti-HER2 therapy as a neoadjuvant treatment for HER2-positive breast cancer.From June 2020 to August 2023, 225 HER2-positive breast cancer patients who underwent radical surgery following neoadjuvant treatment were enrolled in this study.The patients were divided into two groups based on the drugs they received: the nab-paclitaxel group (n=166, receiving nab-paclitaxel + platinum along with trastuzumab and pertuzumab) and the docetaxel group (n=59, receiving docetaxel + platinum along with trastuzumab and pertuzumab). The pathological response and adverse events related to the drugs were collected and evaluated in both groups.In the nab-paclitaxel group, the rates of breast and total pathological complete response (bpCR and tpCR) were significantly greater than those in the docetaxel group (69.27% vs. 47.45%, P=0.003; 68.67% vs. 45.76%, P=0.002). For patients who did not achieve pCR after chemotherapy, the pathological response of chemotherapy was analysed using MP grading and RCB grading. The results showed that there was a statistically significant difference between the two groups (P<0.05). Multivariate analysis revealed that therapeutic drugs, clinical stage, ER status, and Ki-67 level were independent predictors of pCR. The nab-paclitaxel group had a significantly greater proportion of patients with peripheral sensory neuropathy than did the docetaxel group (58.43% vs. 38.98%, P=0.035), while the docetaxel group had a greater proportion of patients with allergies and elevated ALT (31.93% vs. 69.49%, P=0.000; 23.49% vs. 40.68%, P=0.021).Our real-world study revealed that nab-paclitaxel combined with anti-HER2 therapy was an effective neoadjuvant therapy for HER2-positive breast cancer. The multivariate analysis revealed that chemotherapy drugs, clinical stage, ER status, and Ki-67 level was the significant factor influencing treatment outcome. These findings offer a valuable reference for the neoadjuvant treatment of patients with HER2-positive breast cancer.